Biocontrol Stem-end Rot Disease Agent, Alternaria alternata YZU, on Pitaya by Soil Phosphate Solubilizing Bacteria - Trung, Do Quang (VNU Journal of Science: Natural Sciences and Technology; Vol 39 No 2DO - 10.25073/2588-1140/vnunst.5427, 2023)
Biocontrol of stem end disease agent, Alternaria alternata YZU, on pitaya is more interested in altering the application of chemical pesticides. This study was conducted to characterize antagonistic phosphate solubilizing bacteria (PSB) from rhizosphere soil for their biocontrol activities against A. alternata YZU under laboratory and greenhouse conditions. Six PSB isolated from 31 rhizosphere soil samples were tested for inhibiting the mycelial growth of  A. alternata YZU in dual cultures. Six isolates were determined to inhibit the mycelial growth of A. alternata YZU. Among them, PSB31 presented the highest level of antagonistic activity against A. alternata YZU with a mean inhibition diameter of 0.64 ± 0.02 cm, while the other strains, including PSB11, PSB21, PSB41, PSB51, and PSB61 presented a weaker inhibition. The results also showed that the strain PSB31 was identified as Bacillus sp. strain PSB31 (Accession number: ON422095) and could control the mycelial growth of A. alternata YZU by secreting antifungal metabolites. Moreover, an in vivo antagonistic experiment of PSB31 on pitaya twigs showed a significant reduction of lesions on twigs than the control. The results suggested that the isolated PSB31 is a potential biological control agent. Further studies should be done to identify the biochemical basis of their activity against A. alternata YZU.